Musculoskeletal Disorders Complaints by Part Body Fishermen Village Labuang Namrole South Buru District - Masudin Sangaji1, Kuswandi Saalu2, Sahrir Sillehu2, M. Taufan Umasugi2, Johanis Hursepuny2, Tri Nisw (Indian Journal of Forensic Medicine & Toxicology, 2020)
Indonesian people living in coastal areas work as fishermen. Musculoskeletal disorders are felt by fishermen in the muscles and bones resulting in the decreased system of movement. The purpose of the study was to identify differences in musculoskeletal complaints based on body parts. The study design uses observational analytic, using a cross-sectional design. Fishermen’s research samples amounted to 35 people. The results of the majority of respondents aged 51-55 years and 61-65 years, tenure of> 10 years and unnatural work postures. Nordic Body Map (NBM) measurement, musculoskeletal complaints due to unnatural/forced work postures experienced by respondents. Low extremity musculoskeletal complaints with a mean value of 18.8 and the lowest score of 12 while the highest is a score of 20. Conclusions based on the Nordic Body Map (NBM) musculoskeletal complaints occur because of unnatural/forced work postures. The majority of complaints experienced are found in the lower extremities. It is recommended that fishermen dynamically adjust their work positions.